(untitled) (American Journal of Business Management, Economics and Banking, 2025)
Human capital has emerged as a decisive factor in ensuring sustainable economic growth, labor productivity, and national competitiveness in a rapidly evolving global economy. This article explores the theoretical foundations, economic classifications, and contemporary approaches to understanding human capital. Particular attention is given to the relationship between human capital and investment, supported by empirical insights and historical development of the concept. Drawing on the experience of Uzbekistan and global economic theory, the paper discusses how targeted investments in education, health, and training translate into higher productivity and inclusive development. The study concludes with a framework for understanding the formation of human capital through institutional, individual, and innovation-driven mechanisms.